Oral cancer risk behaviours of Indian immigrants in Australia: a qualitative study. (25th November 2021) - Saraswat, Nidhi; Prabhu, Neeta; Pillay, Rona; Everett, Bronwyn; George, Ajesh
Abstract: Objective : Oral cancer is widespread in South Asia, particularly India. In Australia, Indians are one of the fastest‐growing communities. This study aimed to explore the oral cancer‐related knowledge, attitudes and practices of Indian immigrants in Australia. Methods : Fourteen semi‐structured interviews were conducted with Indian immigrants residing across New South Wales and Victoria. Purposive and snowball sampling were used for recruitment. Data were analysed through a directed content analysis approach. Results : All participants were knowledgeable of oral cancer risks associated with tobacco and alcohol, but few were familiar with the harmful effects of areca nut preparations. Varied attitudes were evident with most participants acknowledging the importance of oral cancer check‐ups, yet very few followed this practice. All participants admitted engaging in oral cancer risk practices including areca nut use at least once or more in their lifetime. Conclusion : Oral cancer risk practices are common among Indian immigrants in Australia who possess limited knowledge with varying attitudes in this area. Implications for public health : Preventative strategies are needed to limit the use of oral cancer risk products among Indian immigrants. General practitioners and community organisations can play a key role in raising awareness in this area.